Novel signal transduction and peptide specificity of glucagon-like peptide receptor in 3T3-L1 adipocytes - Montrose-Rafizadeh, Chahrzad; Yang, Huan; Wang, Yihong; Roth, Jesse; Montrose, Marshall H.; Adams, Lisa G. (Journal of cellular physiology, 1997)
Glucagon‐like peptide‐1 (7–36) amide (GLP‐1), in addition to its well known effect of enhancing glucose‐mediated insulin release, has been shown to have insulinomimetic effects and to enhance insulin‐mediated glucose uptake and lipid synthesis in 3T3‐L1 adipocytes. To elucidate the mechanisms of GLP‐1 action in these cells, we studied the signal transduction and peptide specificity of the GLP‐1 response. In 3T3‐L1 adipocytes, GLP‐1 caused a decrease in intracellular cAMP levels which is the opposite to the response observed in pancreatic beta cells in response to the same peptide. In 3T3‐L1 adipocytes, free intracellular calcium was not modified by GLP‐1. Peptide specificity was examined to help determine if a different GLP receptor isoform was expressed in 3T3‐L1 adipocytes vs. beta cells. Peptides with partial homology to GLP‐1 such as GLP‐2, GLP‐1 (1–36), and glucagon all lowered cAMP levels in 3T3‐L1 adipocytes. In addition, an antagonist of pancreatic GLP‐1 receptor, exendin‐4 (9–39), acted as an agonist to decrease cAMP levels in 3T3‐L1 adipocytes as did exendin‐4 (1–39), a known agonist for the pancreatic GLP‐1 receptor. Binding studies using 125I‐GLP‐1 also suggest that pancreatic GLP‐1 receptor isoform is not responsible for the effect of GLP‐1 and related peptides in 3T3‐L1 adipocytes. Based on these results, we propose that the major form of the GLP receptor in 3T3‐L1 adipocytes is functionally different from the pancreatic GLP‐1 receptor. J. Cell. Physiol. 172:275–283, 1997. Published 1997 Wiley‐Liss, Inc. This article was prepared by a group of United States government employees and non‐United States government employees, and as such is subject to 17 U.S.C. Sec. 105.